The Association between Peer Influence and Family Environment and Smoking Behavior among Adolescents - Anshori, Akbar; Ra’uf, Muhammad; Milasari (Fakultas Kedokteran, Universitas Papua, 2025)
Smoking behavior among adolescents constitutes a serious public health concern due to its adverse health effects and its rapid increase among school-aged populations. Adolescents are particularly susceptible to social environmental influences, especially peer influence and the family environment, which may encourage experimentation with smoking and the development of smoking behavior. This study aimed to examine the association between peer influence and family environment and smoking behavior among adolescents at Public Senior High School 4 Banjarmasin. This study employed a quantitative design with a cross-sectional approach. The population consisted of 308 tenth-grade students, and a sample of 175 respondents was selected using simple random sampling. Data were collected using a questionnaire that had undergone validity and reliability testing. The Chi-square test results indicated a significant association between peer influence and smoking behavior (p = 0.001) as well as between family environment and smoking behavior (p = 0.002). Negative peer influence functioned as a protective factor against adolescent smoking behavior, whereas positive peer influence and a family environment with smoking family members increased the risk of smoking initiation. These findings underscore the importance of education, supervision, and active involvement of families and schools in efforts to prevent smoking behavior among adolescents